Peran Social Media Marketing Activities dalam Membangun Brand Equity dengan Mediasi Brand Trust, Brand Image, Brand Awareness pada Produk SOMETHINC di Indonesia - Mochamad Nurhadi; Alif Safira Salsabillah; Tatik Suryani; Abu Amar Fauzi (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
In the digital era, the existence of social media marketing activities is a strong driver for exclusive marketing trends in various industrial sectors, one of which is local product SOMETHINC. The research aims to analyze the role of social media marketing activities in building brand equity and the mediating role of brand awareness, brand image, and brand trust. The data collection method used purposive sampling and obtained data from 258 respondents. Data were analyzed using the Partial Least Square technique with Structure Equation Modeling (PLS-SEM). The results showed that brand trust, brand image, and brand awareness had a significant relationship to brand equity, but social media marketing activities did not significantly shape brand equity. However, the results of the study found that the mediating role of brand trust, brand image, and brand awareness can increase the effectiveness of the role of marketing activities through social media to form brand equity. The research results imply that brand awareness, brand image, and brand trust that consumers have towards SOMETHINC brand are proven to have a positive impact on increasing brand competitiveness in the market. Implementing a targeted and effective marketing strategy will strengthen brand equity in the market.